Chatterjea fixed point theorem in rectangular b-metric space - Limboo, Narendra Prasad; Manandhar, K.B. (Kathmandu University Journal of Science Engineering and Technology, 2026)
In this paper, a Chatterjea-type fixed point theorem in a rectangular b-metric space is proved, thereby providing a complete solution to an open problem posed by Reny George, S. Radenovic, K.P. Reshma and S. Shukla (Rectangular b-metric space and contraction principles).